2019
DOI: 10.2217/epi-2018-0217
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive circRNA/miRNA/mRNA Analysis Reveals circRNAs Protect Against Toxicity Induced by BPA in GC-2 Cells

Abstract: Aim: To identify the circRNAs expression pattern and roles in bisphenol A (BPA) induced germ cell apoptosis. Materials & methods: We performed circRNA/miRNA/mRNA-Seq in 120 μM BPA treated and nontreated GC-2 cells. Bioinformatic analysis, qPCR, apoptosis assays, luciferase report were done in the function analysis. Results: A large number of apoptosis related circRNAs/miRNAs/mRNAs were differentially expressed with competing endogenous RNA network constructed. Interestingly, most investigated upregulated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Analysis of circRNA–miRNA–mRNA coexpression networks is vital in the preliminary prediction of circRNA function and can also implicate the genes involved in core biological functions 34 . A ceRNA network of 12 screened mRNAs (Table 2) was constructed, and we found that eight mRNAs (Pln, Fabp3, Cdh2, Cdk1, Fxyd1, Nprl3, Dkk3 and Cldn15) and five circRNAs (mmu_circ_0001679, mmu_circ_0001212, mmu_circ_0000372, mmu_circ_0001471 and mmu_circ_0000723) may contribute to P2X 7 R antagonism via A‐438079.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of circRNA–miRNA–mRNA coexpression networks is vital in the preliminary prediction of circRNA function and can also implicate the genes involved in core biological functions 34 . A ceRNA network of 12 screened mRNAs (Table 2) was constructed, and we found that eight mRNAs (Pln, Fabp3, Cdh2, Cdk1, Fxyd1, Nprl3, Dkk3 and Cldn15) and five circRNAs (mmu_circ_0001679, mmu_circ_0001212, mmu_circ_0000372, mmu_circ_0001471 and mmu_circ_0000723) may contribute to P2X 7 R antagonism via A‐438079.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of circRNA-miRNA-mRNA coexpression networks is vital in the preliminary prediction of circRNA function and can also implicate the genes involved in core biological functions. 34 A F I G U R E 6 Validation of eight screened mRNAs by RT-qPCR. Expression patterns of eight genes were consistent with the sequencing results.…”
Section: Verification Of Dysregulated Circrnas and Mrnasmentioning
confidence: 99%
“…By using paired-end sequencing, the nucleotide length of sequencing was 150 bp. Single-stranded DNA was generated using 0.1 M NaOH and its loading concentration was 8 pM, which was measured by qPCR (11,12). Sequencing quality was evaluated by FastQC v0.11.7 software (http://www.bioinformatics.…”
Section: Methodsmentioning
confidence: 99%
“…A testis-specific circRNA derived from male sex-determining gene Sry was shown to contain 16 sites for miR-138, acting as its sponge [ 132 ]. Furthermore, circRNAs were shown to respond to toxicity and stress in the germline and may play protective roles in germline development by sponging miRNAs [ 133 , 134 , 135 ].…”
Section: Functions Of Sncrnas During Mammalian Germ Cell Developmentmentioning
confidence: 99%